2017
DOI: 10.1371/journal.pone.0176286
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered probiotic for the treatment of phenylketonuria (PKU); assessment of a novel treatment in vitro and in the PAHenu2 mouse model of PKU

Abstract: Phenylketonuria (PKU) is a genetic disease characterized by the inability to convert dietary phenylalanine to tyrosine by phenylalanine hydroxylase. Given the importance of gut microbes in digestion, a genetically engineered microbe could potentially degrade some ingested phenylalanine from the diet prior to absorption. To test this, a phenylalanine lyase gene from Anabaena variabilis (AvPAL) was codon-optimized and cloned into a shuttle vector for expression in Lactobacillus reuteri 100-23C (pHENOMMenal). Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 26 publications
0
41
0
1
Order By: Relevance
“…Probiotics are live microorganisms that provide health benefits when consumed, including enhancement of gut epithelial barrier function, blocking of pathogen binding, and vitamin synthesis (Hill et al, 2014). There has been increasing success in expanding the therapeutic scope and efficacy of probiotics through genetic engineering, with prior work demonstrating preclinical efficacy against infectious and metabolic diseases (Durrer et al, 2017;Hwang et al, 2017;Isabella et al, 2018;Palmer et al, 2018). Engineered probiotics are exciting platforms for in situ drug synthesis and delivery, provided they maintain appropriate abundance and activity at their target site.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are live microorganisms that provide health benefits when consumed, including enhancement of gut epithelial barrier function, blocking of pathogen binding, and vitamin synthesis (Hill et al, 2014). There has been increasing success in expanding the therapeutic scope and efficacy of probiotics through genetic engineering, with prior work demonstrating preclinical efficacy against infectious and metabolic diseases (Durrer et al, 2017;Hwang et al, 2017;Isabella et al, 2018;Palmer et al, 2018). Engineered probiotics are exciting platforms for in situ drug synthesis and delivery, provided they maintain appropriate abundance and activity at their target site.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the metabolically engineered Lactobacillus reuteri carrying PAL from Anabaena variabilis could greatly reduce blood phenylalanine in the mice model of PKU within 4-5 days of treatment. It also observed that the probiotic microbe was lost from the intestine at 8 months post treatment [43]. Recently, an engineered probiotic SYNB1618 was constructed for degradation of phenylalanine.…”
Section: Engineering Probiotics For Amelioration Of Metabolic Disordersmentioning
confidence: 99%
“…Although we could not find evidence for probiotic use in orotic aciduria, guidelines for the management of methylmalonic and propionic acidemia included the use of probiotics 57 . Furthermore, researchers have demonstrated the benefit of engineered L. reuteri strains in a murine phenylketonuria (PKU) model 58 .…”
Section: Probiotic Approaches To Rare Disease Treatmentmentioning
confidence: 99%